A weather-resistant polyvinyl chloride material and its preparation method
Patent Information
- Application Number
- CN202610793737.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-09-01
AI Technical Summary
然而,PVC大分子链中天然存在热力学不稳定的结构缺陷:烯丙基氯和叔氯结构
1、通过漆酶催化氧化接枝技术,将咖啡酸共价接枝于酶解木质素骨架,制备的L-CA大分子功能体兼具290~400nm宽谱紫外吸收与受阻酚-氮氧自由基协同催化淬灭的双重防护功能,大分子化特征使其不迁移,从根本上解决了光稳定剂的析出失效问题。
Smart Images

Figure CN122668486A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a weather-resistant polyvinyl chloride material and its preparation method. Background Technology
[0002] Polyvinyl chloride (PVC) is a major thermoplastic produced globally, widely used in construction, cables, automobiles, and outdoor facilities. However, PVC macromolecular chains naturally contain thermodynamically unstable structural defects: allyl chloride and tertiary chloride structures. These defects undergo elimination reactions under processing heat or ultraviolet light excitation, releasing hydrogen chloride and generating carbon-carbon double bonds. The conjugated extension of these double bonds forms polyene sequences, which, corresponding to the absorption of visible light, cause the material to yellow or even turn brownish-black. This reaction exhibits strong autocatalytic free radical chain characteristics: the generated hydrogen chloride produces chlorine radicals under light irradiation; these chlorine radicals react with PVC to generate alkyl carbon radicals; these alkyl carbon radicals combine with oxygen to generate peroxide radicals; these peroxide radicals abstract hydrogen to generate hydroperoxides; and the hydroperoxides photolyze to produce new alkoxy radicals and hydroxyl radicals, thus forming a complete photo-oxidation chain reaction. This leads to severe discoloration of the material, a sharp decline in mechanical properties, and a severely insufficient weather resistance.
[0003] Existing weather-resistant PVC systems mainly rely on petroleum-based synthetic light stabilizers and lead salts, organotin, and barium cadmium soaps as heat stabilizers, which have the following fundamental technical defects: First, there is the defect of toxicity. Heavy metal additives such as lead and cadmium, as well as organotin compounds, have persistent ecotoxicity and are continuously released throughout the product's life cycle, endangering human health and the ecological environment, and are subject to strict restrictions under the EU RoHS Directive and REACH Regulation.
[0004] Secondly, there is the defect of migration and precipitation. Phthalate plasticizers, benzotriazole light stabilizers and other small molecule synthetic additives have limited compatibility with PVC. After long-term outdoor use, they migrate to the surface, causing blooming, adhesion and loss of weather protection function. In addition, phthalate plasticizers have endocrine-disrupting properties and are subject to strict regulation.
[0005] Third, functional antagonism defects. Benzotriazole UV absorbers can only block some wavelengths of light, are ineffective against short-wave UV below 290nm, and cannot remove active free radicals already generated inside the material; some sulfur-containing organotin compounds antagonize with light stabilizers, resulting in low overall weather resistance.
[0006] Fourth, the "zinc burning mutation defect". In the calcium-zinc composite thermally stable system, zinc stearate reacts with hydrogen chloride to continuously generate zinc chloride. When zinc chloride accumulates to a critical concentration, its Lewis acid activity triggers a sudden and accelerated degradation, i.e., the zinc burning phenomenon. The processing thermal stability time is usually no more than 50 minutes, and the processing window is extremely narrow.
[0007] Fifth, the non-renewable nature of existing additives. Almost all existing additives are derived from petrochemical resources, resulting in a high carbon footprint and failing to meet the requirements of green chemistry and a circular economy.
[0008] Furthermore, the method of directly blending unmodified lignin into PVC has problems such as extremely poor compatibility with PVC, easy agglomeration forming micron-level defects, serious impact on mechanical properties, difficulty in coloring, and limited free radical scavenging ability, thus failing to achieve a truly functional bio-based substitution.
[0009] In summary, there is currently a lack of a bio-based PVC stabilization system that can simultaneously achieve non-toxic and environmentally friendly properties, no migration or leaching, elimination of zinc burning, and multi-dimensional synergistic weather protection. Summary of the Invention
[0010] To address the shortcomings of the existing technologies, the technical problem to be solved by this invention is to provide a weather-resistant polyvinyl chloride material constructed with a fully bio-based functional additive synergistic stabilizing system and its preparation method, which completely eliminates toxic and harmful substances such as lead, cadmium, and organotin, fundamentally solves the problems of additive migration and precipitation and zinc burning, achieves multiple synergistic protection against ultraviolet rays, heat and oxygen, and free radicals, and at the same time endows the material with mechanical enhancement and barrier enhancement functions.
[0011] In a first aspect, the present invention provides a weather-resistant polyvinyl chloride material, based on 100 parts by weight of polyvinyl chloride powder, comprising the following components: 3-5 parts by weight of lignin-based macromolecular UV blocking-free radical scavenging functional body (L-CA), 6-10 parts by weight of nanocellulose-supported bio-based heat stabilizer (CNC@ZnIta / CaLac), 35-50 parts by weight of bio-based reactive plasticizer (ECP-PLA), 3-5 parts by weight of chitosan quaternary ammonium salt intercalated montmorillonite (CS-MMT), 0.3-0.8 parts by weight of stearic acid, and 0.2-0.5 parts by weight of paraffin wax; The lignin-based macromolecular UV-blocking and free radical scavenging functional body is a macromolecular functional body prepared by grafting caffeic acid onto lignin as the backbone after activating the phenolic hydroxyl groups through a laccase and a synergistic oxidation system of 2,2,6,6-tetramethylpiperidine-1-oxy free radicals. The nanocellulose-supported bio-based heat stabilizer is a composite powder prepared by coordinating and immobilizing zinc itaconic acid and calcium lactate on the surface of nanocellulose whiskers. The bio-based reactive plasticizer is an epoxy-containing reactive plasticizer prepared by transesterification reaction of epoxidized cashew phenol glycidyl ether and hydroxyl-terminated polylactic acid oligomer diol. The chitosan quaternary ammonium salt intercalated montmorillonite is an organically modified montmorillonite prepared by intercalating chitosan, after quaternization modification, into the interlayer of sodium-based montmorillonite via ion exchange.
[0012] Preferably, the grafting rate of caffeic acid in the lignin-based macromolecular UV blocking-free radical scavenging functional body is 15-25 wt%, and the grafting rate is calculated as the ratio of the amount of caffeic acid grafted to the mass of enzymatically hydrolyzed lignin.
[0013] Preferably, the nanocellulose-supported bio-based heat stabilizer, based on dry powder, has a zinc content of 3.5–5.0 wt% and a calcium content of 1.0–2.0 wt%.
[0014] Preferably, the bio-based reactive plasticizer has a retained epoxy value of not less than 0.15 mol / 100g and a viscosity of 800–1500 mPa·s at 25°C.
[0015] Preferably, the weather-resistant polyvinyl chloride material further comprises 0.3 to 0.8 parts by weight of stearic acid and 0.2 to 0.5 parts by weight of paraffin wax.
[0016] Secondly, the present invention provides a method for preparing weather-resistant polyvinyl chloride material, comprising the following steps: Nanocellulose-supported bio-based heat stabilizer, chitosan quaternary ammonium salt intercalated montmorillonite, and lignin-based macromolecular UV blocking-free radical scavenging functional body were premixed and dispersed in a high-speed mixer at 3000 rpm for 10 minutes to obtain a pre-dispersed mixture. The pre-dispersed mixture, bio-based reactive plasticizer, and polyvinyl chloride powder were mixed at 90°C and 1500 rpm for 8 minutes in a mixer to obtain a homogeneous mixture. The uniform mixture is transferred into a two-roll mill and mixed at 175-185°C for 8-10 minutes to allow the chitosan quaternary ammonium salt intercalated montmorillonite sheets to align in the shear field, thereby constructing a biomimetic layered barrier structure and producing sheets. The compound sheet is hot-pressed at 185-195℃ and 10-15 MPa for 5 minutes, and then cooled and demolded while maintaining the pressure to obtain weather-resistant polyvinyl chloride material.
[0017] Preferably, the lignin-based macromolecular UV blocking-free radical scavenging functional group is prepared as follows: Enzymatically hydrolyzed lignin is dissolved in a 0.1 mol / L sodium acetate-acetic acid buffer solution, and a 20 g / L enzymatically hydrolyzed lignin solution is prepared at pH 5.0 and a temperature of 25°C; 2,2,6,6-tetramethylpiperidine-1-oxo radical and laccase are added to the solution, wherein the molar ratio of the 2,2,6,6-tetramethylpiperidine-1-oxo radical to the oxidizable primary hydroxyl groups in the enzymatically hydrolyzed lignin is 0.1. 1. The amount of laccase used is 10U per gram of lignin, and pure oxygen is continuously introduced at a flow rate of 50mL / min. The reaction is stirred at 25°C for 4 hours. Then, caffeic acid is added, and the molar ratio of caffeic acid to the phenolic hydroxyl groups in the hydrolyzed lignin is 0.8:1. Pure oxygen is continuously introduced and the reaction is stirred for 6 hours. The reaction product is washed at least 3 times through an ultrafiltration membrane with a molecular weight cutoff of 10kDa, and then freeze-dried at -50°C and 5Pa for 48 hours to obtain the lignin-based macromolecular UV blocking-free radical scavenging functional powder.
[0018] Preferably, the nanocellulose-supported bio-based heat stabilizer is prepared as follows: microcrystalline cellulose is added to a 64wt% sulfuric acid solution, with a mass-to-volume ratio of microcrystalline cellulose to sulfuric acid solution of 1g:10mL. After hydrolysis at 45℃ for 60 minutes, deionized water is injected to terminate the reaction. The solution is then centrifuged, dialyzed until the pH of the dialysate is greater than 5, and ultrasonically dispersed to obtain a nanocellulose whisker aqueous dispersion with a solid content of 2wt%. Itaconic acid produced by microbial fermentation is reacted with zinc oxide in deionized water at a molar ratio of 2:1 at 70℃ for 2 hours to obtain an aqueous solution of zinc itaconic acid. Lactic acid and calcium carbonate were reacted in deionized water at a molar ratio of 2:1 at 60°C for 1 hour, and then filtered to obtain an aqueous solution of calcium lactate. An aqueous solution of zinc itaconic acid was added dropwise to the aqueous dispersion of nanocellulose whiskers at a molar ratio of zinc ions to carboxyl groups on the surface of nanocellulose whiskers of 1:1, and stirred at room temperature for 4 hours. Then, an aqueous solution of calcium lactate was added dropwise at a molar ratio of calcium ions to hydroxyl groups on the surface of nanocellulose whiskers of 0.5:1, and stirred at room temperature for 2 hours. The resulting dispersion was spray-dried at an inlet air temperature of 180°C and an outlet air temperature of 90°C to obtain the nanocellulose-supported bio-based heat stabilizer powder.
[0019] Preferably, the bio-based reactive plasticizer is prepared as follows: cashew nut shell powder and m-chloroperoxybenzoic acid are dissolved in dichloromethane at a molar ratio of 1:1.1, mixed at 0°C, and then heated to room temperature with stirring for 12 hours. After alkali washing, drying, and vacuum distillation, epoxidized cashew nut shell powder glycidyl ether with an epoxy value of not less than 0.35 mol / 100 g is obtained; L-lactic acid is ring-opening polymerized under vacuum at 140°C with 0.1 wt% stannous octoate as a catalyst, and the number of fractions is controlled to be uniform. The molecular weight is 500-1000 g / mol, and hydroxyl-terminated polylactic acid oligomer diol is obtained. The epoxidized cashew phenol glycidyl ether and the hydroxyl-terminated polylactic acid oligomer diol are mixed at a ratio of epoxy equivalent to hydroxyl equivalent of 1:0.5. Tetrabutyl titanate is added at 0.5 wt% of the total mass of the reactants. The mixture is reacted at 180°C under nitrogen protection for 3 hours. Byproducts are removed by vacuum distillation to obtain the bio-based reactive plasticizer with an epoxy value of not less than 0.15 mol / 100 g.
[0020] Preferably, the chitosan quaternary ammonium salt intercalated montmorillonite is prepared as follows: chitosan with a degree of deacetylation of not less than 85% and a weight-average molecular weight of 50,000–100,000 g / mol is dissolved in a 1 wt% acetic acid aqueous solution to prepare a 2 wt% chitosan solution; glycidyltrimethylammonium chloride is added, with a molar ratio of glycidyltrimethylammonium chloride to chitosan amino groups of 1.2:1; the mixture is stirred at 60°C for 12 hours to obtain a chitosan quaternary ammonium salt solution with a degree of quaternization of not less than 70%; cation exchange capacity is then... Sodium-based montmorillonite at a concentration of 90–110 meq / 100g was added to deionized water and stirred at 80°C for 4 hours to obtain a 3 wt% montmorillonite dispersion. The chitosan quaternary ammonium salt solution was slowly added dropwise to the montmorillonite dispersion at a dosage of 1.2 times the cation exchange capacity of montmorillonite, and stirred at 80°C for 4 hours. After filtration, the solution was washed with deionized water until the filtrate was free of chloride ions, dried at 80°C for 24 hours, and ground through a 200-mesh sieve to obtain chitosan quaternary ammonium salt intercalated montmorillonite powder with an interlayer spacing of not less than 2.0 nm.
[0021] Compared with existing technologies, the beneficial effects of this invention are: 1. By using laccase-catalyzed oxidation grafting technology, caffeic acid is covalently grafted onto the enzymatic hydrolysis lignin skeleton. The prepared L-CA macromolecular functional body has dual protective functions of broadband ultraviolet absorption of 290-400 nm and synergistic catalytic quenching of hindered phenol-nitrogen radicals. Its macromolecular characteristics prevent it from migrating, fundamentally solving the problem of light stabilizer precipitation failure.
[0022] 2. By coordinating and immobilizing zinc itaconic acid and calcium lactate on the surface of nanocellulose whiskers, a triple dynamic equilibrium thermally stable system is constructed, consisting of HCl neutralization, ZnCl2 coordination passivation, and calcium-zinc metathesis regeneration. This completely eliminates the zinc burn-off mutation phenomenon in the calcium-zinc system and extends the thermal stability time to more than 120 minutes.
[0023] 3. ECP-PLA reactive plasticizer can undergo an in-situ nucleophilic ring-opening reaction with the active allyl chloride on the chain during PVC processing to form a covalent ether bond anchor, permanently eliminating plasticizer migration, and simultaneously achieving in-situ repair of PVC degradation defect sites, blocking the zipper-like deHCl reaction.
[0024] 4. Through layered micro-nano blending process, a multi-level biomimetic barrier structure with alternating L-CA chemical barrier layer / CNC fiber network layer / CS-MMT oriented sheet layer is constructed in PVC matrix, which can significantly reduce the penetration rate of O2 and water (the penetration rate can be reduced to less than 1 / 23 of the original system), significantly slow down the internal photo-oxidation rate of the material, and at the same time give the material excellent mechanical reinforcement effect. Attached Figure Description
[0025] Figure 1 This is a schematic diagram illustrating the causal relationship chain of the core defects in the existing polyvinyl chloride weather-resistant system.
[0026] Figure 2 This is a schematic diagram of the entire preparation process of the weather-resistant polyvinyl chloride material of the present invention.
[0027] Figure 3 This is a schematic diagram of the functional structural units of the L-CA macromolecule and its dual protection mechanism.
[0028] Figure 4 A schematic diagram of the dynamic thermal stability equilibrium mechanism of a bio-based thermal stabilizer immobilized on nanocellulose.
[0029] Figure 5 This is a schematic diagram of the in-situ covalent anchoring and defect repair mechanism of bio-based reactive plasticizers.
[0030] Figure 6 This is a schematic diagram of the layered micro-nano blending process and the biomimetic layered barrier structure.
[0031] Figure 7 This is a schematic diagram of the collaborative protection mechanism of the four functional subsystems. Detailed Implementation
[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0033] Example 1 A weather-resistant polyvinyl chloride (PVC) material, based on 100 parts by weight of PVC powder, comprises the following components: 3-5 parts by weight of lignin-based macromolecular UV-blocking and free radical scavenging functional body (L-CA), 6-10 parts by weight of nanocellulose-supported bio-based heat stabilizer (CNC@ZnIta / CaLac), 35-50 parts by weight of bio-based reactive plasticizer (ECP-PLA), 3-5 parts by weight of chitosan quaternary ammonium salt intercalated montmorillonite (CS-MMT), 0.3-0.8 parts by weight of stearic acid, and 0.2-0.5 parts by weight of paraffin wax.
[0034] Specifically, the lignin-based macromolecular UV-blocking-radical-scavenging functional body (L-CA) is a macromolecular functional body prepared by covalently grafting caffeic acid onto the phenolic hydroxyl sites of lignin using enzymatically hydrolyzed lignin (EHL) as the backbone and through a laccase / 2,2,6,6-tetramethylpiperidine-1-oxygen radical (TEMPO) catalytic oxidation system; the caffeic acid grafting rate (calculated as the ratio of the amount of caffeic acid grafted to the mass of enzymatically hydrolyzed lignin) is 15-25 wt%.
[0035] Specifically, the nanocellulose-supported bio-based heat stabilizer (CNC@ZnIta / CaLac) is composed of zinc itaconic acid (ZnIta) and calcium lactate (CaLac) coordinated and supported on the surface of nanocellulose whiskers (CNC); the Zn content is 3.5-5.0 wt% and the Ca content is 1.0-2.0 wt% based on the mass of the dried powder.
[0036] Specifically, the bio-based reactive plasticizer (ECP-PLA) is prepared by transesterification of epoxidized cashew phenol glycidyl ether (ECP, epoxy value not less than 0.35 mol / 100g) and hydroxyl-terminated polylactic acid oligomer diol (PLA-diol, number average molecular weight of 500-1000 g / mol). The product retains an epoxy value of not less than 0.15 mol / 100g and a viscosity of 800-1500 mPa·s at 25°C.
[0037] Specifically, the chitosan quaternary ammonium salt intercalated montmorillonite (CS-MMT) is prepared by intercalating chitosan quaternary ammonium salt (CS-Q, with a quaternization degree of not less than 70%) into the interlayer of sodium-based montmorillonite through cation exchange, with the interlayer spacing being... Not less than 2.0nm.
[0038] It should be noted that the above four functional components correspond to the four functional subsystems of this invention, and the technical principles and synergistic relationships of each subsystem are as follows: In this embodiment, the design of the L-CA subsystem is based on the following dual protection mechanism, such as... Figure 3 As shown.
[0039] Mechanism 1 (UV Shielding): The aromatic ring in the lignin phenylpropane unit undergoes a π-π* transition with the conjugated carbonyl / double bond system, exhibiting strong broadband absorption of UV light in the 290–400 nm range. This harmlessly dissipates light energy through thermal vibrations, preventing UV photons from exciting the PVC chain and causing photo-oxidation. Grafted caffeic acid (3,4-dihydroxycinnamic acid) further expands the conjugated system, extending the absorption band to nearly 400 nm, achieving full UV coverage.
[0040] Mechanism 2 (Free Radical Capture-Regeneration Cycle): The phenolic hydroxyl groups of lignin and the o-dihydroxyl groups of caffeic acid act as hydrogen atom donors, providing hydrogen atoms to alkyl radicals (R·) and peroxy radicals (ROO·), terminating the chain reaction (hydrogen donation chain scission mechanism). The residual nitroxide radicals (≡NO·) formed during the oxidation of TEMPO groups can mimic the Denisov cycle of hindered amine light stabilizers: nitroxide radicals react with carbon radicals (R·) to generate hydroxylamine ethers (≡N-OR), which decompose and regenerate nitroxide radicals under light or heat, realizing a catalytic quenching cycle of free radicals, thus giving it a durable and regenerable anti-aging function.
[0041] The specific preparation process of the above-mentioned L-CA functional group is as follows: Dissolve the enzymatically hydrolyzed lignin in 0.1 mol / L sodium acetate-acetic acid buffer (pH=5.0) to prepare a lignin solution with a concentration of 20 g / L. Stir thoroughly at 25°C until completely dissolved to obtain the enzymatically hydrolyzed lignin buffer solution for later use. Add TEMPO (the molar ratio of TEMPO to the oxidizable primary hydroxyl groups in enzymatically hydrolyzed lignin is 0.1:1, based on catalytic amount) to the above buffer solution, then add laccase (10U of laccase per gram of enzymatically hydrolyzed lignin), continuously purify the reaction system with pure O2 (flow rate of 50mL / min), and stir the reaction at 25℃ for 4 hours to allow the laccase / TEMPO system to selectively oxidize the primary hydroxyl groups of the lignin side chain to aldehyde or carboxyl groups, while activating phenolic hydroxyl sites, in preparation for subsequent grafting. Caffeic acid was dissolved in a small amount of ethanol and added to the above reaction system. The molar ratio of caffeic acid to phenolic hydroxyl groups in enzymatically hydrolyzed lignin was 0.8:1. The reaction was continued for 6 hours with O2 stirring. Laccase catalyzed the oxidative coupling grafting reaction between caffeic acid and phenolic hydroxyl groups in lignin to form CC or CO covalent bonds, thus obtaining the caffeic acid grafted lignin intermediate product (L-CA crude product). The crude L-CA product solution was repeatedly ultrafiltered and washed (at least 3 times, with 3 times the volume of deionized water added each time) through an ultrafiltration membrane with a molecular weight cutoff of 10 kDa to remove unreacted small molecule caffeic acid, TEMPO residue and oligomers. The ultrafiltration retentate is the purified L-CA solution. The purified L-CA solution was pre-frozen at -20°C and then placed in a freeze dryer to dry at -50°C and 5 Pa for 48 hours to obtain brown L-CA powder, which was then sealed and stored for later use. The caffeic acid grafting rate of the L-CA powder was 15–25 wt% (quantitatively confirmed by elemental analysis and UV-Vis spectroscopy).
[0042] In this embodiment, the technical principle of the subsystem nanocellulose-supported bio-based heat stabilizer is as follows: Zinc itacate (ZnIta) and calcium lactate (CaLac) are in-situ intercalated and immobilized on the surface of nanocellulose whiskers (CNC) to construct a nanocellulose-supported carboxylate heat stabilizer. This achieves long-term thermal stability by eliminating zinc burning through a triple synergistic mechanism. Figure 4 As shown.
[0043] Mechanism 1 (HCl neutralization): Lactate ions immobilized on the CNC surface (Lac - ) and itaconic acid (Ita²) - As a basic group, it rapidly undergoes a metathesis reaction with HCl produced during the dehydrochlorination of PVC to generate CaCl2 and ZnCl2, instantly eliminating the autocatalytic effect of HCl.
[0044] Mechanism 2 (ZnCl2 coordination passivation): The abundant hydroxyl (-OH) and carboxyl (-COOH) groups on the CNC surface bind the ZnCl2 produced by HCl neutralization through coordination bonds, transforming the highly active ZnCl2 into a stable complex, causing it to lose its Lewis acid activity and completely eliminating the critical effect triggered by zinc burning.
[0045] Mechanism 3 (Calcium-Zinc Metathesis Regeneration): Immobilized calcium lactate (CaLac2) undergoes a metathesis reaction with ZnCl2 (CaLac2+ZnCl2→ZnLac2+CaCl2), regenerating the thermally stable zinc soap (ZnLac2). At the same time, CaCl2 does not have Lewis acid activity, maintaining a dynamic equilibrium cycle of HCl neutralization-ZnCl2 coordination passivation-calcium-zinc metathesis regeneration, achieving an ultra-long thermal stability time.
[0046] The specific preparation process of the above-mentioned nanocellulose-supported bio-based heat stabilizer is as follows: Microcrystalline cellulose (MCC) was added to a 64 wt% sulfuric acid solution (MCC to acid mass-volume ratio of 1 g: 10 mL) and hydrolyzed at 45 °C for 60 minutes. The hydrolysate was then injected into a large amount of deionized water to terminate the reaction. After centrifugation (8000 rpm, 10 min), dialysis (molecular weight cutoff of 14 kDa until the pH of the dialysate was greater than 5), and ultrasonic dispersion (400 W, 15 min), a CNC aqueous dispersion with a solid content of 2 wt% and a pH of 4.5 was obtained. Itaconic acid produced by microbial fermentation was mixed with ZnO in deionized water at a molar ratio of 2:1, and the mixture was stirred at 70°C for 2 hours until completely dissolved to obtain an aqueous solution of zinc itaconic acid (ZnIta) (Zn²⁺). + (Concentration 0.1 mol / L); Lactic acid and CaCO3 were mixed in deionized water at a molar ratio of 2:1, stirred at 60°C for 1 hour, and excess CaCO3 was removed by filtration to obtain an aqueous solution of calcium lactate (CaLac) (Ca²⁺). + (Concentration 0.1 mol / L) Add Zn² to the CNC dispersion + A ZnIta aqueous solution was added dropwise to the CNC surface at a molar ratio of 1:1 to the carboxyl groups, and stirred at room temperature for 4 hours to allow Zn²⁺ to form a soluble compound. + Zn²⁺ undergoes coordination adsorption with sulfonic acid and carboxyl groups on the CNC surface. + The ZnIta-supported intermediate dispersion was obtained by immobilizing it on the CNC surface. Add Ca²⁺ to the above dispersion + A CaLac aqueous solution was added dropwise at a molar ratio of 0.5:1 to the hydroxyl groups on the CNC surface, and the mixture was stirred at room temperature for 2 hours. + Further immobilization was achieved through hydrogen bonding synergistic effect, resulting in CNC@ZnIta / CaLac composite dispersion; The composite dispersion was spray-dried at an inlet air temperature of 180℃ and an outlet air temperature of 90℃ to obtain a white to light yellow CNC@ZnIta / CaLac composite powder, which was then sealed and stored for later use. The Zn content was 3.5–5.0 wt% and the Ca content was 1.0–2.0 wt% (quantitatively confirmed by inductively coupled plasma atomic emission spectrometry) based on the mass of the dried powder.
[0047] In this embodiment, the technical principle of the subsystem bio-based reactive plasticizer is as follows. The design of the ECP-PLA reactive plasticizer is based on the following molecular engineering strategy, and its in-situ anchoring and defect repair mechanism is as follows: Figure 5 As shown, specifically; Strategy 1 (Flexible long chains impart plasticizing effect): The C15 alkyl side chain of cashew phenol provides sufficient molecular chain segment freedom, which can be inserted between PVC molecular chains to reduce the glass transition temperature of the material and achieve a plasticizing effect; the long non-polar segment at the same time reduces the polarity difference with PVC and improves the compatibility between the two. Strategy 2 (In-situ covalent anchoring by active epoxy groups): The epoxy groups retained in the ECP-PLA molecule undergo nucleophilic ring-opening reactions with the allyl chloride residues exposed by the trace amount of HCl removal in PVC at the PVC processing temperature (160-180℃), forming stable ether covalent anchor points, which permanently fix the plasticizer molecule to the PVC chain, fundamentally eliminating the migration and precipitation of plasticizer; Strategy 3 (In-situ Repair of Defect Sites): The epoxy group preferentially reacts with the degradation defect site (allyl chloride), converting the active and unstable chlorine atom into a stable ether bond, preventing the site from continuing to initiate a zipper-like deHCl reaction, and achieving in-situ repair of the initial degradation defect.
[0048] The specific preparation process of the above-mentioned bio-based reactive plasticizer is as follows: Cashew nut shell phenol (purity not less than 95%) and m-chloroperoxybenzoic acid (m-CPBA, molar amount 1.1 times that of cashew nut shell phenol) were dissolved in dichloromethane. The mixture was stirred at 0°C and then slowly heated to room temperature for 12 hours to induce peroxy acid epoxidation of the terminal olefin double bond in the cashew nut shell phenol side chain, yielding an epoxidized cashew nut shell phenol intermediate containing an epoxy group. The solvent was removed by vacuum distillation, and the product was washed with a saturated sodium bicarbonate aqueous solution and dried to obtain epoxidized cashew nut shell phenol glycidyl ether (ECP) with an epoxy value not less than 0.35 mol / 100 g (determined according to HG / T2-485 method). L-lactic acid was ring-opening polymerized at 140°C under vacuum conditions with stannous octoate (0.1 wt%) as a catalyst, and the number average molecular weight was controlled between 500 and 1000 g / mol to obtain hydroxyl-terminated polylactic acid oligomer diol (PLA-diol). ECP and PLA-diol were mixed at a ratio of 1:0.5 (epoxy equivalent of ECP to hydroxyl equivalent of PLA-diol). Tetrabutyl titanate (0.5 wt% of the total mass of reactants) was added as a catalyst. The mixture was reacted at 180 °C under nitrogen protection for 3 hours, resulting in an ester exchange reaction. The terminal hydroxyl groups of PLA-diol were exchanged with the ester groups of ECP, while some epoxy groups were retained (the target retained epoxy value is not less than 0.15 mol / 100g), thus obtaining the ECP-PLA reactive plasticizer. The byproduct small molecule lactic acid was removed by vacuum distillation (120℃, below 1kPa) to obtain a pale yellow, transparent, viscous liquid, ECP-PLA, with a viscosity of 800-1500 mPa·s at 25℃. It was sealed and stored for later use.
[0049] In this embodiment, the technical principle of chitosan quaternary ammonium salt intercalated montmorillonite is as follows: When high aspect ratio montmorillonite sheets (aspect ratio greater than 100) are highly oriented in the PVC matrix, O2 and water molecules are forced to travel along tortuous paths, significantly increasing the effective diffusion path length and thus reducing the gas permeation rate. According to the Cussler tortuous path model, the quantitative relationship between the effective diffusion coefficient and the bulk diffusion coefficient of the sheet filler in the polymer matrix is: ; in, The effective diffusion coefficient in the composite material is expressed in m² / s. is the bulk diffusion coefficient in unfilled PVC, in m² / s; The aspect ratio of the sheet filler is the ratio of the sheet diameter to its thickness. (CS-MMT) Approximately 100-200; The volume fraction of the lamellar filler in the composite material is 0.03 to 0.05 (i.e., 3 to 5 vol%). when hour, This means that the penetration rate of O2 and water is reduced by about 23 times, which can greatly slow down the photo-oxidation rate inside the material.
[0050] Chitosan quaternary ammonium salt intercalation modification can increase the interlayer spacing of montmorillonite from about 1.2 nm in the original sodium-based montmorillonite to no less than 2.0 nm, which is beneficial for the further exfoliation and orientation of montmorillonite sheets in the PVC matrix and fully utilizes its tortuous path barrier effect.
[0051] The specific preparation process of the above-mentioned chitosan quaternary ammonium salt intercalated montmorillonite is as follows: Chitosan (degree of deacetylation not less than 85%, weight-average molecular weight 50,000–100,000 g / mol) was dissolved in a 1 wt% aqueous acetic acid solution to prepare a 2 wt% chitosan solution. Glycidyltrimethylammonium chloride (GTMAC, molar amount 1.2 times the molar amount of chitosan amino groups) was added to the solution, and the mixture was stirred at 60°C for 12 hours to induce ring-opening quaternization, converting the chitosan amino groups into quaternary ammonium groups (—N). + (CH3)3), to obtain a chitosan quaternary ammonium salt (CS-Q) solution, with a quaternization degree of not less than 70% (quantitatively confirmed by 1H NMR spectroscopy). Sodium-based montmorillonite (cation exchange capacity of 90-110 meq / 100g) was added to deionized water and stirred at 80°C for 4 hours to allow it to fully swell, resulting in a 3wt% montmorillonite dispersion. The CS-Q solution was slowly added dropwise to the montmorillonite dispersion. The amount of CS-Q added was 1.2 times the cation exchange capacity of montmorillonite (i.e., CS-Q equivalent to 1.2 molar amounts of cation exchange capacity was added per 100g of montmorillonite). The mixture was stirred at 80℃ for 4 hours. The quaternary ammonium groups of CS-Q then reacted with the Na+ in the montmorillonite interlayer. + Cation exchange occurs, and CS-Q inserts into the interlayer of montmorillonite to obtain CS-MMT suspension; The CS-MMT suspension was filtered and washed with deionized water until no Cl- was found in the filtrate. - (Tested with silver nitrate solution), dried at 80℃ for 24 hours, ground, and passed through a 200-mesh sieve to obtain CS-MMT powder. Interlayer spacing was determined by X-ray diffraction (XRD). The wavelength should be no less than 2.0 nm to prove that the intercalation was successful.
[0052] It should also be noted that in some embodiments, tannic acid is used instead of caffeic acid to prepare L-CA functional compounds, and tannic acid (tannic acid) can replace caffeic acid as the grafted natural phenolic acid. Tannic acid contains multiple galloyl groups and has the ability to donate hydrogen at multiple points in polyphenols, theoretically providing stronger free radical scavenging efficiency; the grafting ratio can be adjusted to a molar ratio of tannic acid to phenolic hydroxyl groups in enzymatically hydrolyzed lignin of 0.3:1 (due to the large molecular weight of tannic acid, the stoichiometric ratio is adjusted accordingly). The laccase / TEMPO oxidation grafting process route remains unchanged. When using this alternative, care should be taken to control the grafting amount to avoid excessive cross-linking of the lignin skeleton, which would lead to poor dispersibility of L-CA in PVC.
[0053] It should also be noted that in some embodiments, zinc gluconate can be used instead of zinc itaconic acid, and calcium citrate can be used instead of calcium lactate. Gluconic acid can be prepared by the oxidation of glucose (a product of corn fermentation). Zinc gluconate has better water solubility and stronger chelation coordination ability with the CNC surface; calcium citrate has three carboxyl groups, which can form multi-point hydrogen bonds with the CNC surface, resulting in better immobilization stability. The CNC immobilization process route and spray drying steps remain unchanged. When adopting this alternative, the economic rationale between the raw material cost of zinc gluconate and the performance improvement should be comprehensively evaluated.
[0054] The present invention discloses a weather-resistant polyvinyl chloride material, which in this embodiment is based on 100 parts by weight of polyvinyl chloride powder (K value 67-70). Typical formulation composition is shown in Table 1; Table 1
[0055] Based on the table above, specifically, using 100 parts by weight of polyvinyl chloride powder (K value 67-70) as a reference, the following components are weighed according to the formula: 40 parts by weight of bio-based reactive plasticizer, 4 parts by weight of L-CA functional agent, 8 parts by weight of nanocellulose-supported bio-based heat stabilizer, 4 parts by weight of chitosan quaternary ammonium salt intercalated montmorillonite, 0.5 parts by weight of stearic acid, and 0.3 parts by weight of paraffin wax.
[0056] Eight parts by weight of nanocellulose-supported bio-based heat stabilizer, four parts by weight of chitosan quaternary ammonium salt intercalated montmorillonite, and four parts by weight of L-CA functional group were added to a high-speed mixer and pre-mixed at 3000 rpm for 10 minutes to obtain a pre-dispersed mixture, preventing the nano-components from agglomerating. The pre-dispersed mixture was then added to a mixer along with 40 parts by weight of bio-based reactive plasticizer, 0.5 parts by weight of stearic acid, 0.3 parts by weight of paraffin wax, and 100 parts by weight of polyvinyl chloride powder. The mixture was then high-speed mixed at 90°C and 1500 rpm for 8 minutes to ensure the additives uniformly coated the polyvinyl chloride particles, resulting in a homogeneous mixture.
[0057] The homogeneous mixture is transferred to a two-roll mill and mixed at 175–185°C for 8–10 minutes. The shear field drives the chitosan quaternary ammonium salt intercalated montmorillonite sheets to align within the polyvinyl chloride matrix, constructing a multi-level biomimetic barrier structure consisting of an L-CA chemical barrier layer, a nanocellulose fiber network layer, and alternating chitosan quaternary ammonium salt intercalated montmorillonite oriented sheets. The resulting sheet is then extruded. The mixed sheet is placed in a flat vulcanizing machine and hot-pressed at 185–195°C and 10–15 MPa pressure for 5 minutes. After cooling to room temperature while maintaining pressure, it is demolded to obtain weather-resistant polyvinyl chloride material products.
[0058] In addition, taking this embodiment as an example, the weather-resistant polyvinyl chloride material prepared according to the above typical formulation was tested using the following methods, and the results are shown in the table below: Table 2
[0059] Weather resistance testing was conducted according to ISO 4892-2 standard, using a xenon arc lamp accelerated aging chamber (irradiance of 0.51 W / m² at 340 nm wavelength) for 3000 hours of cyclic irradiation. The change in yellow index before and after the test was no greater than 4.2, the tensile strength retention rate was no less than 92%, and the elongation at break retention rate was no less than 88%. Thermal stability time was determined using the Congo red method (polyvinyl chloride is mixed on a two-roll mill at 200℃, with the endpoint being the change in Congo red test paper from red to blue). Dynamic thermal stability was measured. The test time is no less than 120 minutes, and there is no sudden zinc burning phenomenon during the entire test process; the mechanical properties are tested according to GB / T1040 (tensile), GB / T1843 (impact), and GB / T9341 (bending), and the notched impact strength is increased by 35% and the flexural modulus is increased by 20% compared with unmodified PVC; the migration is tested according to GB / T13483, and after 100 cycles of aging-condensation alternation at 90℃ and 85% relative humidity, the surface gloss retention rate is no less than 95%, and there is no additive precipitation.
[0060] Example 2 It should also be noted that this invention provides a method for preparing weather-resistant polyvinyl chloride (PVC) materials, specifically involving the blending preparation of weather-resistant PVC materials. This stage employs a layered micro-nano blending process to construct a multi-level biomimetic barrier structure in a PVC matrix, alternating between an L-CA chemical barrier layer, a CNC fiber network layer, and CS-MMT oriented sheets. The complete process flow and final structure are illustrated below. Figure 6 As shown.
[0061] The specific preparation process is as follows: Nanocellulose-supported bio-based heat stabilizer, chitosan quaternary ammonium salt intercalated montmorillonite, and lignin-based macromolecular UV blocking-free radical scavenging functional body were premixed and dispersed in a high-speed mixer at 3000 rpm for 10 minutes to obtain a pre-dispersed mixture. The pre-dispersed mixture, bio-based reactive plasticizer, and polyvinyl chloride powder were mixed at 90°C and 1500 rpm for 8 minutes in a mixer to obtain a homogeneous mixture. The uniform mixture is transferred into a two-roll mill and mixed at 175-185°C for 8-10 minutes to allow the chitosan quaternary ammonium salt intercalated montmorillonite sheets to align in the shear field, thereby constructing a biomimetic layered barrier structure and producing sheets. The compound sheet is hot-pressed at 185-195℃ and 10-15 MPa for 5 minutes, and then cooled and demolded while maintaining the pressure to obtain weather-resistant polyvinyl chloride material.
[0062] Example 3 Based on the above, the synergistic protection pathway of the four functional subsystems against the three major aging factors—ultraviolet radiation, heat, and oxygen—is as follows: Figure 7 As shown.
[0063] In this embodiment, as Figure 7 As shown, ultraviolet radiation is primarily shielded by L-CA through broadband UV absorption, while a small amount of free radicals excited by penetration are quenched by the Denisov cycle catalytic quenching of L-CA. Thermal effects during processing and use are addressed jointly by the triple dynamic equilibrium mechanism of CNC@ZnIta / CaLac and the defect site repair of ECP-PLA. Oxygen permeation is first significantly reduced by the physical tortuous path barrier of CS-MMT, and the remaining trace amounts of O2 are then treated by the free radical quenching mechanism of L-CA. These four subsystems complement each other and synergistically enhance each other, forming a complete, multi-dimensional protection system.
Claims
1. A weather-resistant polyvinyl chloride material, characterized in that, Based on 100 parts by weight of polyvinyl chloride powder, the following components are included: 100 parts by weight of polyvinyl chloride powder with a K value of 67-70; 3-5 parts by weight of lignin-based macromolecular UV blocking and free radical scavenging functional body; 6-10 parts by weight of nanocellulose-supported bio-based heat stabilizer; 35-50 parts by weight of bio-based reactive plasticizer; and 3-5 parts by weight of chitosan quaternary ammonium salt intercalated montmorillonite. The lignin-based macromolecular UV-blocking and free radical scavenging functional body is a macromolecular functional body prepared by grafting caffeic acid onto lignin as the backbone after activating the phenolic hydroxyl groups through a laccase and a synergistic oxidation system of 2,2,6,6-tetramethylpiperidine-1-oxy free radicals. The nanocellulose-supported bio-based heat stabilizer is a composite powder prepared by coordinating and immobilizing zinc itaconic acid and calcium lactate on the surface of nanocellulose whiskers. The bio-based reactive plasticizer is an epoxy-containing reactive plasticizer prepared by transesterification reaction of epoxidized cashew phenol glycidyl ether and hydroxyl-terminated polylactic acid oligomer diol. The chitosan quaternary ammonium salt intercalated montmorillonite is an organically modified montmorillonite prepared by intercalating chitosan, after quaternization modification, into the interlayer of sodium-based montmorillonite via ion exchange.
2. A method for preparing the weather-resistant polyvinyl chloride material according to claim 1, characterized in that, Includes the following steps: Nanocellulose-supported bio-based heat stabilizer, chitosan quaternary ammonium salt intercalated montmorillonite, and lignin-based macromolecular UV blocking-free radical scavenging functional group were pre-mixed and dispersed in a high-speed mixer at 3000 rpm for 10 minutes to obtain a pre-dispersed mixture. The pre-dispersed mixture, bio-based reactive plasticizer, and polyvinyl chloride powder were mixed at 90°C and 1500 rpm for 8 minutes in a mixer to obtain a homogeneous mixture. The uniform mixture is transferred into a two-roll mill and mixed at 175-185°C for 8-10 minutes to allow the chitosan quaternary ammonium salt intercalated montmorillonite sheets to align in the shear field, thereby constructing a biomimetic layered barrier structure and producing sheets. The compound sheet is hot-pressed at 185-195℃ and 10-15 MPa for 5 minutes, and then cooled and demolded while maintaining the pressure to obtain weather-resistant polyvinyl chloride material.
3. The weather-resistant polyvinyl chloride material according to claim 1, characterized in that, The grafting rate of caffeic acid in the lignin-based macromolecular UV blocking-free radical scavenging functional body is 15-25 wt%, and the grafting rate is expressed as the ratio of the amount of caffeic acid grafted to the mass of enzymatically hydrolyzed lignin.
4. The weather-resistant polyvinyl chloride material according to claim 1, characterized in that, The nanocellulose-supported bio-based heat stabilizer, based on dry powder, has a zinc content of 3.5–5.0 wt% and a calcium content of 1.0–2.0 wt%.
5. The weather-resistant polyvinyl chloride material according to claim 1, characterized in that, The bio-based reactive plasticizer has a retained epoxy value of not less than 0.15 mol / 100g and a viscosity of 800–1500 mPa·s at 25°C.
6. The method according to claim 2, characterized in that, The lignin-based macromolecular UV blocking-free radical scavenging functional group was prepared as follows: Enzymatically hydrolyzed lignin was dissolved in a 0.1 mol / L sodium acetate-acetic acid buffer solution, and a 20 g / L lignin hydrolyzed solution was prepared at pH 5.0 and 25°C. 2,2,6,6-Tetramethylpiperidine-1-oxo radical and laccase were added to the solution, wherein the molar ratio of the 2,2,6,6-tetramethylpiperidine-1-oxo radical to the oxidizable primary hydroxyl groups in the enzymatically hydrolyzed lignin was 0.1:
1. The amount of laccase used was 10U per gram of lignin, and pure oxygen was continuously introduced at a flow rate of 50mL / min. The reaction was stirred at 25°C for 4 hours. Then, caffeic acid was added, with a molar ratio of caffeic acid to phenolic hydroxyl groups in the hydrolyzed lignin of 0.8:
1. Pure oxygen was introduced and the reaction was stirred for another 6 hours. The reaction product was washed at least 3 times through an ultrafiltration membrane with a molecular weight cutoff of 10kDa, and then freeze-dried at -50°C and 5Pa for 48 hours to obtain the lignin-based macromolecular UV blocking-free radical scavenging functional powder.
7. The method according to claim 2, characterized in that, The nanocellulose-supported bio-based heat stabilizer was prepared as follows: Microcrystalline cellulose was added to a 64wt% sulfuric acid solution, with a mass-to-volume ratio of cellulose to sulfuric acid of 1g:10mL. Hydrolysis was carried out at 45℃ for 60 minutes, followed by the injection of deionized water to terminate the reaction. The solution was then centrifuged, dialyzed until the dialysate pH was greater than 5, and ultrasonically dispersed to obtain a nanocellulose whisker aqueous dispersion with a solid content of 2wt%. Itaconic acid produced by microbial fermentation was reacted with zinc oxide in deionized water at a molar ratio of 2:1 at 70℃ for 2 hours to obtain an aqueous solution of zinc itaconic acid. The emulsion... Acid and calcium carbonate were reacted in deionized water at a molar ratio of 2:1 at 60°C for 1 hour, and then filtered to obtain an aqueous solution of calcium lactate. An aqueous solution of zinc itaconic acid was added dropwise to the aqueous dispersion of nanocellulose whiskers at a molar ratio of zinc ions to carboxyl groups on the surface of nanocellulose whiskers of 1:1, and stirred at room temperature for 4 hours. Then, an aqueous solution of calcium lactate was added dropwise at a molar ratio of calcium ions to hydroxyl groups on the surface of nanocellulose whiskers of 0.5:1, and stirred at room temperature for 2 hours. The resulting dispersion was spray-dried at an inlet air temperature of 180°C and an outlet air temperature of 90°C to obtain the nanocellulose-supported bio-based heat stabilizer powder.
8. The method according to claim 2, characterized in that, The bio-based reactive plasticizer is prepared as follows: cashew nut shell powder and m-chloroperoxybenzoic acid are dissolved in dichloromethane at a molar ratio of 1:1.1, mixed at 0°C, and then heated to room temperature with stirring for 12 hours. After alkali washing, drying, and vacuum distillation, epoxidized cashew nut shell powder glycidyl ether with an epoxy value of not less than 0.35 mol / 100 g is obtained. L-lactic acid is ring-opening polymerized under vacuum at 140°C with 0.1 wt% stannous octoate as a catalyst, and the number average molecular weight is controlled. The concentration of the polymer is 500-1000 g / mol, yielding hydroxyl-terminated polylactic acid oligomer diol. The epoxidized cashew phenol glycidyl ether and the hydroxyl-terminated polylactic acid oligomer diol are mixed at a ratio of epoxy equivalent to hydroxyl equivalent of 1:0.
5. 0.5 wt% tetrabutyl titanate is added, and the mixture is reacted at 180°C under nitrogen protection for 3 hours. Byproducts are removed by vacuum distillation to obtain the bio-based reactive plasticizer with an epoxy value of not less than 0.15 mol / 100 g.
9. The method according to claim 2, characterized in that, The chitosan quaternary ammonium salt intercalated montmorillonite is prepared as follows: chitosan with a degree of deacetylation of not less than 85% and a weight-average molecular weight of 50,000–100,000 g / mol is dissolved in a 1 wt% acetic acid aqueous solution to prepare a 2 wt% chitosan solution. Glycidyltrimethylammonium chloride is added, with a molar ratio of glycidyltrimethylammonium chloride to chitosan amino groups of 1.2:
1. The mixture is stirred at 60°C for 12 hours to obtain a chitosan quaternary ammonium salt solution with a degree of quaternization of not less than 70%. A cation exchange capacity of… Sodium-based montmorillonite (90-110 meq / 100g) was added to deionized water and stirred at 80°C for 4 hours to obtain a 3wt% montmorillonite dispersion. The chitosan quaternary ammonium salt solution was slowly added dropwise to the montmorillonite dispersion at a dosage of 1.2 times the cation exchange capacity of montmorillonite, and stirred at 80°C for 4 hours. After filtration, the solution was washed with deionized water until the filtrate was free of chloride ions, dried at 80°C for 24 hours, and ground through a 200-mesh sieve to obtain chitosan quaternary ammonium salt intercalated montmorillonite powder with an interlayer spacing of not less than 2.0 nm.
10. The weather-resistant polyvinyl chloride material according to claim 1, characterized in that, It also contains 0.3 to 0.8 parts by weight of stearic acid and 0.2 to 0.5 parts by weight of paraffin.